2019
DOI: 10.1113/jp277618
|View full text |Cite
|
Sign up to set email alerts
|

PKA phosphorylation underlies functional recruitment of sarcolemmal SK2 channels in ventricular myocytes from hypertrophic hearts

Abstract: Key points Small‐conductance Ca 2+ ‐activated K + (SK) channels expressed in ventricular myocytes are dormant in health, yet become functional in cardiac disease. SK channels are voltage independent and their gating is controlled by intracellular [Ca 2+ ] in a biphasic manner. Submicromolar [Ca 2+ ] activates the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 74 publications
(148 reference statements)
6
42
1
Order By: Relevance
“…As SK channels appears to play a role in some pathological conditions in the ventricles (Gui ; Bonilla ; Hundahl ; Chen ; Hamilton ), it could be speculated that the SK channels also have a contributory role in the pathogenesis of CaM‐associated LQTS. Three out of the four LQTS‐associated CaM variants significantly down‐regulated the SK current, with CaM D130G being the variant most profoundly decreasing SK current with no effect on the trafficking of the channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As SK channels appears to play a role in some pathological conditions in the ventricles (Gui ; Bonilla ; Hundahl ; Chen ; Hamilton ), it could be speculated that the SK channels also have a contributory role in the pathogenesis of CaM‐associated LQTS. Three out of the four LQTS‐associated CaM variants significantly down‐regulated the SK current, with CaM D130G being the variant most profoundly decreasing SK current with no effect on the trafficking of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…This atrial selectivity makes SK channels an interesting target in the treatment of atrial arrhythmias, as the ventricular side effects have been speculated to be avoided (Xu ; Diness , ; Skibsbye ; Skibsbye ). However, several recent studies have shown that SK channel current also becomes functional in the ventricles during enhanced sympathetic activation through β ‐adrenergic stimulation (Chen ; Hamilton ).…”
Section: Introductionmentioning
confidence: 99%
“…This regulation seems C-terminal specific, since SK trafficking is not altered when the three "major" Serine residues are replaced by non-phosphorable amino acids. On the other hand, PKA phosphorylation of the fourth carboxyl Serine is associated with a functional upregulation of SK2 in hypertrophic rat cardiomyocytes (Hamilton et al, 2020). In murine colonic myocytes, the open probability of SK channels is increased after phosphorylation by calmodulin kinase II (Kong et al, 2000).…”
Section: Small Conductance Calcium Activated Potassium Channels (Sk1mentioning
confidence: 99%
“…I SK is an outward current which also increases with the intracellular Ca 2+ concentration, and thus I SK promotes negative Ca 2+ -to-APD coupling. Under normal conditions, I SK only presents in atrial myocytes, but under heart failure, it also presents in ventricular myocytes [ 51 53 ]. Since the charge carriers of both currents are not Ca 2+ , unlike I Ca and I NCX , they do not directly affect intracellular Ca 2+ dynamics.…”
Section: Resultsmentioning
confidence: 99%